A RARE CASE OF SEROUS CARCINOMA OF THE UTERINE CORPUS THAT ARISES IN POLYP - Kocevska, Ana; Bajalski, Emil; Georgiev, Dimitar; Ismaili, Bashkim; Skeparovska, Kristina; Tahir, Shenol; Nakov, Aleksandar (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Endometrial polyps (EPs) are common pathological findings and their prevalence range is between 16% to 34% depending on characteristics of the examined population and detecting methods. Clinically, these lesions cause thickening of the endometrium and abnormal uterine bleeding. Asymptomatic EPs can be detected by routine ultrasound examination or infertility investigations. Most EPs are benign. Their malignant potential is highest in postmenopausal women with uterine bleeding (2.3%). Serous carcinoma is the prototype of type-II endometrial cancer (nonendometrioid) and accounts for <10% of all endometrial carcinomas. It is a very aggressive tumor, unrelated to estrogen stimulation, arising occasionally in endometrial polyps or from precancerous lesions developing in atrophic endometrium that mainly occur in older women. We present a case of 72-years-old patient with uterine bleeding, with thick and heterogenous endometrium detected on ultrasound. Fractionated explorative curretage was performed and serous carcinoma that arises in polyp was diagnosed. After operative treatment, histopathological analysis of the operative material showed stage II of the disease. Keywords: endometrial polyps, abnormal uterine bleeding, serous carcinoma, endometrial thickening. https://doi.org/10.55302/JMS2251044k